Ovarian reserve after salpingectomy: a systematic review and meta-analysis - Mohamed, Ahmed Aboelfadle; Yosef, Ali Haroun; James, Cathryn; Al-Hussaini, Tarek Khalaf; Bedaiwy, Mohamed Ali; Amer, Saad A. (Wiley, 2017)
Introduction